Rethinking Arab American activism - Pennock, Pamela E., author. Link
1 online resource.
Keywords: "Rethinking Arab American Activism analyzes the long-overlooked political activities of Arab Americans in the United States, uncovering a rich history that dispels common misconceptions that Arab American activism emerged only in the aftermath of the September 11th attacks of 2001. Pennock chronicles how the Arab-Israeli Wars of 1967 and 1973 galvanized a wave of secular, leftist activism. Grassroots organizing in cities like Detroit and the formation of organizations such as the Organization of Arab Students and the Association of Arab American University Graduates illustrated this era of political awakening in the 1960s and 1970s. These groups formed coalitions with African Americans and other minority groups, and Arab American activism transitioned into more mainstream political realms during the 1980s and 1990s to address civil rights, anti-imperialism, and anti-discrimination efforts. Following September 11th, Arab Americans faced increased scrutiny and discrimination but also found new avenues for activism and coalition-building. By shedding light on the enduring and diverse contributions of Arab Americans to U.S. socio-political landscapes, the book also explores the legacy of that period of organizing for contemporary justice activism on Palestinian rights. This volume provides a comprehensive yet concise history for readers interested in Arab American history, the history of social movements and activism, and contemporary American history"--